Sales Force Management - Johnston, Mark W.; Marshall, Greg W. (New York, 2011)
The tenth edition of Sales Force Management, a significant milestone in the history of this book, carries on the tradition from previous editions, incorporating the latest research and management practices into an easy-to-read yet comprehensive learning tool. You will notice many changes as new, innovative learning tools are integrated with the latest in sales management theory and practice. At the same time, we have taken great care to preserve the excellent framework and principles from editions one through nine. In short, we have taken the best from earlier editions and added relevant, real-world student learning tools and up-to-date sales management theory and practice to create this tenth edition of Sales Force Management.
Keywords: Sales management